Intra- and Post-Complications of Cervical Laminoplasty for the Treatment of Cervical Myelopathy: An Analysis of a Nationwide Database. Issue 20 (15th October 2020) - Mesregah, Mohamed Kamal; Buchanan, Ian A.; Formanek, Blake; Wang, Jeffrey C.; Buser, Zorica
Abstract : Study Design: Retrospective database study. Objective: To assess the intra- and postoperative complications of cervical laminoplasty and to evaluate the effect of intraoperative neuromonitoring use on postoperative limb paralysis incidence. Summary of Background Data: Cervical laminoplasty is a known procedure for the management of cervical spondylotic myelopathy (CSM). Methods: This was a retrospective study of 532 patients with CSM who underwent cervical laminoplasty between 2007 and the first quarter of 2016 using the Humana subset of the PearlDiver Database. The database was queried using the relevant International Classification of Diseases (ICD-9 and ICD-10) codes for CSM and Current Procedural Terminology (CPT) codes for cervical laminoplasty. The intra- and postoperative incidence of surgical and medical complications and reoperations was then determined and was compared with a propensity score-matched cohort of patients who had posterior laminectomy and fusion (490 patients in each group), using multivariate logistic regression analysis. Results: Laminoplasty was associated with a lower incidence of dysphagia (odds ratio [OR] = 0.37, 95% confidence interval [CI] = 0.16–0.79; P = 0.014), 30-day readmission (OR = 0.51, 95% CI = 0.35–0.75; P < 0.001), urinary tract infection (OR = 0.58, 95% CI = 0.37–0.93; P = 0.023), and incision and drainage, exploration or evacuation (OR = 0.28, 95% CI = 0.08–0.79; P = 0.026). The use of intraoperative neuromonitoring was associated with a non-significant lower incidence of limb paralysis within 1 and 3 months postoperatively (OR = 0.52 and 0.51, 95% CI = 0.23–1.19 and 0.23–1.11; P = 0.119 and 0.091, respectively). Conclusion: Compared with posterior laminectomy and fusion, laminoplasty had lower rates of dysphagia, urinary tract infection, and 30-day readmission. The use of intraoperative neuromonitoring was associated with a lower risk of postoperative limb paralysis, but it did not achieve statistical significance. Level of Evidence: 4